Assembly of Sub‐Crystals on the Macroscale and Construction of Composite Building Units on the Microscale for SAPO‐34. Issue 20 (20th September 2018) - Yuan, Delin; Xing, Aihua; Miao, Ping; Sun, Qi; Cui, Lishan; Wang, Hui; Ma, Linge; Chiang, FuKuo; Kong, Jiechen
Abstract: The nucleation and growth of SAPO‐34 crystals with triethylamine (TEA) as a single template was monitored with ex situ time‐resolved characterization methods. The investigation focused on the evolution of the intermediate phases at different crystallization stages of SAPO‐34. The morphology transformation of the intermediate phases at different crystallization times revealed the unique self‐assembly process of the sub‐crystals. The cubic SAPO‐34 crystals can be constructed from eight pyramidal subunits. Additionally, the construction order of cha cages and double‐six‐membered ring ( d6r ) units in the initial crystallization stage was determined. The appearance of cha cages prior to d6r units can be attributed to the structure‐directing effect of protonated TEA, which is charge balanced with the negative charge of the framework from Si incorporation. Further analysis showed that Si species were incorporated into the framework by direct participation in the initial crystallization stage and substitution for framework P atoms during the later stage. Abstract : Construction crew : A SAPO‐34 crystallization mechanism has been studied that includes the self‐assembly of sub‐crystals and the construction of composite building units (see figure).